(3CHjGJ oeNJGQI ef TQM GdUaOj Ydi dGejI GdYLe ddWZQGFjs - (3eMeO Hf Ydj GdbGQGfj GdOeTbjs; (3GdUaOj , UdGM GdOjf Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf GdUaOj,J (B764 (3g` s ((3GdSjO eMeO Hf Ydj GdbGQGfj GdeOeTbj s)
(3ChdgG (B:s
(3CJQc ghi GdCJQGc s
(3BNQgG (B:s
(3hdQH fGRdI jVjb dgG GdaJi PQYkG hYfO Gddg efgG GdeNQL VGbJ adeG ESJMceJ MdbGJgG oaQLJ hcfJ CXfgG dG JaQL s
(3GNJGQ gPg GdCHjGJ fGSNgGs
(3hcJH aj ChdgG haj GdHWGbI GdeUhQI eYgG OjhGf GdUaOj NWCs
(3ofSNJ gPg GdCHjGJ ef TQM dGejI GdYLe JCdja UdGM GdOjf Hf Ndjd GdUaOj Hf CjHc GdUaOjs
(3hQO CjVkG JMJ Qbe (B2202 s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdCOHs